MODEL PENCEGAHAN CEDERA TIDAK DISENGAJA PADA ANAK BALITA DI RUMAH TANGGA DKI JAKARTA DENGAN METODE MODEL SOSIO EKOLOGI - Irma YUNIATI; Gama Widyaputra; Lelitasari . (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Injuries are a major health problem that causes millions of deaths each year. Most injuries in children are unintentional, mainly due to falls and household accidents. Lack of knowledge and parental supervision are important risk factors, so a prevention model based on the Socio-Ecological Model Method is needed at the household level. This study used a mixed method by distributing questionnaires to 400 research samples. Data analysis methods were univariate, bivariate, and multivariate. This study found 16 types of unintentional injuries in toddlers in DKI Jakarta, with the highest prevalence being falls (20%), collisions (16%), insect bites (16%), slips (8%), and abrasions/bruises (7%). Prevention was carried out using the Socio-Ecological Model Method, which covers the individual, interpersonal, community, and social levels. Through health education, parents are expected to be able to recognise dangers, prevent injuries, and provide first aid for household accidents, thereby reducing the incidence of unintentional injuries in toddlers. Ongoing research, updating of Riskesdas data, increasing public awareness, and developing a pocket guide on preventing injuries to toddlers at home are required.